2008
DOI: 10.4007/annals.2008.168.1011
|View full text |Cite
|
Sign up to set email alerts
|

On the classification of isoparametric hypersurfaces with four distinct curvatures in spheres

Abstract: In this paper we give a new proof for the classification result in [3]. We show that isoparametric hypersurfaces with four distinct principal curvatures in spheres are of Clifford type provided that the multiplicities m 1 , m 2 of the principal curvatures satisfy m 2 ≥ 2m 1 − 1. This inequality is satisfied for all but five possible pairs (m 1 , m 2 ) with m 1 ≤ m 2 . Our proof implies that for (m 1 , m 2 ) = (1, 1) the Clifford system may be chosen in such a way that the associated quadratic forms vanish on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…On the other hand, in S n+1 , there are many more examples (cf. [5,12,18,42,44]). Münzner ([30, 31]) showed that the number r of distinct principal curvatures of an isoparametric hypersurface in S n+1 must be 1, 2, 3, 4 or 6.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in S n+1 , there are many more examples (cf. [5,12,18,42,44]). Münzner ([30, 31]) showed that the number r of distinct principal curvatures of an isoparametric hypersurface in S n+1 must be 1, 2, 3, 4 or 6.…”
Section: Introductionmentioning
confidence: 99%
“…After this, Immervoll [72] gave a different proof of the theorem of Cecil, Chi and Jensen using isoparametric triple systems. The use of triple systems to study isoparametric hypersurfaces was introduced in a series of papers in the 1980's by Dorfmeister and Neher [45,46,47,48,49,50].…”
Section: Multiplicities Of the Principal Curvatures Of Fkm-hypersurfacesmentioning
confidence: 99%
“…It has been proven that every foliation in round spheres by isoparametric hypersurfaces with 4 principal curvatures is either homogeneous or of FKM type, except possibly for a finite number of isolated cases (cf. [10]).…”
mentioning
confidence: 99%